1997
DOI: 10.1093/emboj/16.11.3341
|View full text |Cite
|
Sign up to set email alerts
|

Second pathway for completion of human DNA base excision-repair: reconstitution with purified proteins and requirement for DNase IV (FEN1)

Abstract: Two forms of DNA base excision‐repair (BER) have been observed: a ‘short‐patch’ BER pathway involving replacement of one nucleotide and a ‘long‐patch’ BER pathway with gap‐filling of several nucleotides. The latter mode of repair has been investigated using human cell‐free extracts or purified proteins. Correction of a regular abasic site in DNA mainly involves incorporation of a single nucleotide, whereas repair patches of two to six nucleotides in length were found after repair of a reduced or oxidized abasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
557
3
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 715 publications
(587 citation statements)
references
References 60 publications
17
557
3
3
Order By: Relevance
“…In contrast, a repair patch size of 2-8 deoxynucleotides was observed initially in reconstituted BER systems and subsequently in vivo, which was named long-patch BER (LP-BER). During in vitro repair of an AP site analog, lacking the aldehyde group, Polb could not remove the APE-generated 5′ blocking group via its dRP lyase activity [77][78][79][80]. Matsumoto's and Dogliotti's groups first showed that such a 5′ blocking group could be removed by the 5′-flap endonuclease 1 (FEN-1) normally required for removing the 5′ RNA primers from Okazaki fragments during DNA replication.…”
Section: Two Basic Modes Of Ber: Sn-vs Lp-bermentioning
confidence: 99%
“…In contrast, a repair patch size of 2-8 deoxynucleotides was observed initially in reconstituted BER systems and subsequently in vivo, which was named long-patch BER (LP-BER). During in vitro repair of an AP site analog, lacking the aldehyde group, Polb could not remove the APE-generated 5′ blocking group via its dRP lyase activity [77][78][79][80]. Matsumoto's and Dogliotti's groups first showed that such a 5′ blocking group could be removed by the 5′-flap endonuclease 1 (FEN-1) normally required for removing the 5′ RNA primers from Okazaki fragments during DNA replication.…”
Section: Two Basic Modes Of Ber: Sn-vs Lp-bermentioning
confidence: 99%
“…Since Rad27 cleaves 5' flaps in long patch BER [25] and has been implicated in NHEJ of ends with 5' flaps both in vivo and in vitro [20,21], we hypothesized that this nuclease might catalyze 5' dRP removal in the absence of the Pol4 lyase ( Figure 1B). We sought to test rejoining of 5' dRP-containing DSBs in pol4Δ rad27Δ double mutants, which would lack both the putative short and long patch NHEJ pathways.…”
Section: Yeast Can Rejoin 5' Drp-containing Dsbs In the Absence Of Bomentioning
confidence: 99%
“…In these cases, the modified AP-site is repaired via the longpatch base excision repair (LP-BER) pathway in which pol-b, d or e incorporates 2-15 nucleotides displacing the strand containing the modified AP-site. The DNA flap structure is cleaved by Fen-1, and the nick is sealed by a DNA ligase (Bambara et al, 1997;Klungland and Lindahl 1997).…”
Section: Introductionmentioning
confidence: 99%